Classifying Children's Behaviour at the Dentist-What about 'Burnout'? - Christopher C. Donnell (MDPI AG, 2023)
In children and young people, complex and prolonged dental treatment can sometimes be met with resistance despite previously successful treatment appointments. While this has traditionally been referred to as a 'loss of cooperation' or 'non-compliance', these children may actually be experiencing 'burnout', of which many may have the potential to recover and complete their course of treatment. Burnout has been defined as "the extinction of motivation or incentive, especially where one's devotion to a cause or relationship fails to produce the desired results". Traditionally, burnout is experienced by those who deliver services rather than be in receipt of a service; however, the burnout concept proposed in this paper explores it as an alternative perspective to other dentally relevant psychosocial conditions and should be considered when employing appropriate behaviour management techniques and coping strategies for paediatric patients. The intention of this paper is not to establish firm grounds for this new concept in healthcare, but to start a discussion and motivate further theoretical and empirical research. The introduction of the 'burnout triad model' and the importance of communication aims to highlight the tripartite influence of patients, parents and professionals engaged in the central 'care experience' and underlines the belief that early recognition and management of potential signs of burnout may help reduce the likelihood of those involved developing the condition.